2019
DOI: 10.1210/clinem/dgz072
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Semaglutide for Type 2 Diabetes by Race and Ethnicity: A Post Hoc Analysis of the SUSTAIN Trials

Abstract: Context Variations in the prevalence and etiology of type 2 diabetes (T2D) across race and ethnicity may affect treatment responses. Semaglutide is a glucagon-like peptide-1 analog approved for once-weekly, subcutaneous treatment of T2D. Objective To compare semaglutide efficacy and safety in race and ethnicity subgroups across the SUSTAIN trials. Design Post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 30 publications
0
19
0
2
Order By: Relevance
“…Absolute weight loss was smaller in the Asian subpopulation treated with semaglutide compared with other race groups in a pooled analysis across the SUSTAIN 1–5 and 7 trials 34 . Similarly, the absolute weight loss obtained by patients in this trial was smaller than in the global SUSTAIN 2 trial with a similar trial design 20 ; this could be explained by a lower baseline body weight for patients included in the present trial (the relative [%] weight loss was of a similar magnitude to that of the global trials) as well as the different trial durations (56 weeks for SUSTAIN 2 vs. 30 weeks for the present trial).…”
Section: Discussionmentioning
confidence: 97%
“…Absolute weight loss was smaller in the Asian subpopulation treated with semaglutide compared with other race groups in a pooled analysis across the SUSTAIN 1–5 and 7 trials 34 . Similarly, the absolute weight loss obtained by patients in this trial was smaller than in the global SUSTAIN 2 trial with a similar trial design 20 ; this could be explained by a lower baseline body weight for patients included in the present trial (the relative [%] weight loss was of a similar magnitude to that of the global trials) as well as the different trial durations (56 weeks for SUSTAIN 2 vs. 30 weeks for the present trial).…”
Section: Discussionmentioning
confidence: 97%
“…In our study, the mean HbA1c reduction in the PEX168/200 μg group was 1.34%. Some previous studies of long‐acting GLP‐1 RAs had similar HbA1c reductions: 1.33% with liraglutide monotherapy (0.9 mg) for 26 weeks in Japanese patients, 12 1.48% with dulaglutide monotherapy (1.5 mg) for 26 weeks in East Asian patients, 13 1.53% with once‐weekly exenatide (2.0 mg) for 26 weeks in a diverse patient population (67% Caucasian, 12.4% East Asian), 14 and 2.0% with semaglutide (1.0 mg) for 30 weeks in Asian patients 15 …”
Section: Discussionmentioning
confidence: 99%
“…31 A post hoc analysis of the SUSTAIN trials revealed that semaglutide was associated with minor reductions or no change in lipid levels across all race and ethnicity subgroups in the SUSTAIN 1 to 7 trials. 32 However, clinical trials on exenatide showed that treatment with exenatide twice-daily or once-weekly significantly improved lipids in Asian and white patients. Asian and white patients showed significant reductions from baseline in the levels of LDL-C and small but statistically significant increases in HDL-C levels (except for Asian patients treated with exenatide onceweekly).…”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial on lixisenatide showed that there were no clinically meaningful changes in lipid variables during the 24‐ and 52‐week treatment periods 31 . A post hoc analysis of the SUSTAIN trials revealed that semaglutide was associated with minor reductions or no change in lipid levels across all race and ethnicity subgroups in the SUSTAIN 1 to 7 trials 32 . However, clinical trials on exenatide showed that treatment with exenatide twice‐daily or once‐weekly significantly improved lipids in Asian and white patients.…”
Section: Discussionmentioning
confidence: 99%